2017
DOI: 10.7150/jbm.17794
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Pattern of Serum Lipid Parameters and a Biological Anti-Oxidant Potential Between Premenopausal and Perimenopausal Healthy Women

Abstract: Objectives. Improved understanding of the associations among cardiometabolic, antioxidative, and menopausal status is crucial to prevent cardiovascular disease (CVD). For preventing the development of CVD in women, the association of serum lipid profile and antioxidant parameters during menopausal transition is of interest. The aim of the study is to evaluate the correlation between lipid and antioxidant levels especially in premenopausal and perimenopausal women. Methods. A total of 130 CVD-free healthy women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Estrogen may also has the ability to upregulate antioxidant gene expression. This was confirmed by a previous study which reported that the antioxidant gene expression was reduced in postmenopausal women and restored by estrogen replacement (Chen & Kotani, ).…”
Section: Discussionsupporting
confidence: 86%
“…Estrogen may also has the ability to upregulate antioxidant gene expression. This was confirmed by a previous study which reported that the antioxidant gene expression was reduced in postmenopausal women and restored by estrogen replacement (Chen & Kotani, ).…”
Section: Discussionsupporting
confidence: 86%